If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + -53 = 2 Reorder the terms: -53 + 5n = 2 Solving -53 + 5n = 2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '53' to each side of the equation. -53 + 53 + 5n = 2 + 53 Combine like terms: -53 + 53 = 0 0 + 5n = 2 + 53 5n = 2 + 53 Combine like terms: 2 + 53 = 55 5n = 55 Divide each side by '5'. n = 11 Simplifying n = 11
| (-2+3(-x-3)-4)+5x=10 | | 7z-5b+8+6b+5z+3= | | X+3=8+10 | | 8-3w=4(w-3)+6 | | X+3=8n+10n | | (-2+3(-x-3)-4)-(-5x)=10 | | 5(3x-7)-(6x+2)7=59 | | h(x)=x^4+6x^2+4ifh(-1) | | cos(x)*cosh(x)=0 | | 2(x-3)=4(x+1)-5 | | h(x)=x^4+6x^2+4 | | 9x+3-10=-5 | | x^3+y^2=64 | | 3y^2-5y+4+y^2-7y-6= | | 0.87=log(x) | | -5/x=75 | | 28.9kg=lb | | -x-6+5x=10 | | -20=10[y+2] | | 7x=9+68 | | K-2/2=-7 | | 12x=12/35 | | 33.333/3=6/t | | 33.3/3=6/t | | 3r-11=25 | | 7k+21=0 | | 20=5y+25 | | log(2)(3x-7)=3 | | 3x^4-3x^3+2x^2-x+10=0 | | y+5=-(x-4) | | 1x-3x=36 | | 16+5x-2=4-5x |